Potensi Pasar Tradisional Blimbing Bagi Masyarakat Di Sekitar Kecamatan Lowokwaru Kota Malang - Rahmad Yusuf Susanto (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2018)
This research conducted in Blimbing traditional  market, Lowokwaru districts, Malang City, which aims to determine the potential of Blimbing traditional market in Lowokwaru districts from the point of view of (1) Employment, (2) Communities income, (3)Capital market education. The type of the research belong to the descriptive study sampling taken technique ProporsionalRandom Sampling, with a sample of 50people. The sample is peope there, merchants livingaround the Blimbing market, collecting data through observation and direct observation from the field by distributing questionnaires.This research resulted in several conclussions : (1) The potential market for employment in traditional Blimbing market Lowokwaru districts  working as merchant in general, (2) The potential market for the average income of the people in Blimbing traditional market Lowokwaru districts more than Rp.3000.000, (3) The education place of capital market to the people living in Blimbing area, Lowokwaru districts, Malang City.